2006
DOI: 10.1124/jpet.106.103242
|View full text |Cite
|
Sign up to set email alerts
|

Improved Left Ventricular Function and Reduced Necrosis after Myocardial Ischemia/Reperfusion in Rabbits Treated with Ranolazine, an Inhibitor of the Late Sodium Channel

Abstract: Ranolazine is an inhibitor of the late sodium current and, via this mechanism, decreases sodium-dependent intracellular calcium overload during ischemia and reperfusion. Ranolazine reduces angina, but there is little information on its effects in acute myocardial infarction. The aim of this study was to test the effects of ranolazine on left ventricular (LV) function and myocardial infarct size after ischemia/reperfusion in rabbits. Ten minutes before coronary artery occlusion (CAO), anesthetized rabbits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Reperfusion is also thought to increase Na ϩ influx by washing out extracellular protons, which reactivates Na ϩ /H ϩ exchange, which has been attenuated by accumulation of extracellular protons after long-sustained ischemia. The contribution of these mechanisms of Na ϩ overload to myocardial necrosis has been supported by the findings that inhibition of the Na ϩ /H ϩ exchanger or Na ϩ channel during ischemia-reperfusion significantly limits myocardial infarct size (9,18).…”
Section: Contribution Of Suppression Of Gap Junction-meditated Injurymentioning
confidence: 52%
“…Reperfusion is also thought to increase Na ϩ influx by washing out extracellular protons, which reactivates Na ϩ /H ϩ exchange, which has been attenuated by accumulation of extracellular protons after long-sustained ischemia. The contribution of these mechanisms of Na ϩ overload to myocardial necrosis has been supported by the findings that inhibition of the Na ϩ /H ϩ exchanger or Na ϩ channel during ischemia-reperfusion significantly limits myocardial infarct size (9,18).…”
Section: Contribution Of Suppression Of Gap Junction-meditated Injurymentioning
confidence: 52%
“…41 Furthermore, the pulmonary circulation would be affected by myocardial dysfunction after MIR. 8,42 Our hemodynamic findings indicating high LVEDP and the lung WD ratio suggest that pulmonary edema influences oxidative stress in the lungs after MIR, and our immunohistochemical studies using an anti-biopyrrin antibody revealed biopyrrin expression in relatively large mononuclear cells located in thickened alveolar walls. Because pulmonary oxidative stress is evoked by the NADPH pathway in cells of the alveolar wall after lung congestion, 43 lung edema could cause bilirubin oxidation by superoxide generated in mononuclear cells.…”
Section: Discussionmentioning
confidence: 98%
“…This could be achieved by inhibiting I NHE or late I Na . Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202].…”
Section: Discussionmentioning
confidence: 99%